2015
DOI: 10.1177/1065912915578460
|View full text |Cite
|
Sign up to set email alerts
|

The Pacifying Effects of Local Religious Institutions

Abstract: This paper tests whether local religious institutions have a dampening effect on the probability of communal violence. It argues that a dense layer of institutions strengthens horizontal and vertical contacts and networks within religious communities. Horizontal linkages help to bridge social, economic, and ethnic divisions. Vertical contacts enable religious leaders to stay informed about communal grievances among their followers and to coordinate conflict resolution attempts. In our analysis of more than 60,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(10 citation statements)
references
References 43 publications
1
9
0
Order By: Relevance
“…Third, we find evidence on the criminal behavior approach of Becker (1968) and Ehrlich (1973) that a larger income gap between individuals (proxied by Gini ratio) can increase criminality. Our results are also in line with the earlier empirical findings in the context of advanced countries (Atems 2020;Choe 2008), (Wu and Wu 2012), as well as developing countries (Enamorado et al 2016;de Hoyos et al 2016), (Imrohoroglu et al 2004) including Indonesia (Cameron and Shah 2014;De Juan et al 2015;Nguyen 2019). Our evidence suggests that government efforts to close the income gap are fundamental to social cohesion (lower crime).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Third, we find evidence on the criminal behavior approach of Becker (1968) and Ehrlich (1973) that a larger income gap between individuals (proxied by Gini ratio) can increase criminality. Our results are also in line with the earlier empirical findings in the context of advanced countries (Atems 2020;Choe 2008), (Wu and Wu 2012), as well as developing countries (Enamorado et al 2016;de Hoyos et al 2016), (Imrohoroglu et al 2004) including Indonesia (Cameron and Shah 2014;De Juan et al 2015;Nguyen 2019). Our evidence suggests that government efforts to close the income gap are fundamental to social cohesion (lower crime).…”
Section: Discussionsupporting
confidence: 91%
“…Higher levels of unequal income distribution were significant determinants of violence related to elections or justice, although no significant effect on crime was found. De Juan et al (2015) also found that vertical and horizontal inequalities could be a source of violence in Indonesia. These studies are relevant considering that increasing welfare disparity in Indonesia could be associated with the rising levels of criminal activities and violence.…”
Section: Literature Reviewmentioning
confidence: 97%
See 1 more Smart Citation
“…In Indonesia, conflicts frequently revolve on differences in religious views (Arifianto, 2021;Harahap et al, 2018;Hasan, 2017). Adherents of indigenous religion are susceptible to confrontation with the broader population (Cao, Duan, Liu, & Wei, 2018;De Juan, Pierskalla, & Vüllers, 2015;Hasanah, Widianto, & Gita Purwasih, 2021;Syarifudin, 2021). One of them is Dayak Hindu Budha Bumi Segandu Indramayu, also known as Dayak Indamayu.…”
Section: Introductionmentioning
confidence: 99%
“…Scholars of religion and conflict have devoted great attention to different aspects of the role of belief systems in processes of contestation (Brubaker, 2015; Smith, 1992), ranging from civil war and terrorism to, more recently, nonviolent contestation and religion's contribution to peace processes (Basedau et al, 2016; De Juan et al, 2015). We know that conflicts with a religious component last longer, are more difficult to resolve, and involve a greater number of casualties (Vüllers et al, 2015).…”
Section: Introductionmentioning
confidence: 99%